Sustainable development as a profit paradox of the small industries of the state of Rondonia - Bueno, Joel (2017)
The concept of sustainable development has become an inevitable reference for political leaders and international organisations. According to its institutional promoters, sustainable development must combine three aspects that are imperative: growth, reduction of poverty and preservation of ecosystems. Combining these imperatives represents hard work and can be difficult for small industrial businesses. Together they are responsible for the economy of a region in the way they involve themselves in society and directly contribute to the country’s growth as well as economic and social development. There is still no clear definition of the factors influencing the economic results of small enterprises which implement social and economic management with corporate social responsibility. Therefore, it is the aim of this paper to elaborate on this paradox, by looking into Small and Medium-sized enterprises which follow that management model, checking whether it is possible to combine economic development and social development and still obtain more profitability. This research refers tothe important study area of sustainability because it focus on industries which are based in the South of Legal Amazon.